STRATEGI PEMBELAJARAN DALAM MENGATASI KENDALA BELAJAR STATISTIKA DI MASA PANDEMI COVID-19 - KOEKOEH HARDJITO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Statistics courses have their uniqueness in the eyes of students. On the one hand, this course is very important in supporting research activities, on the other hand, it is still considered a difficult subject to learn. Obstacles in studying statistics are increasing with the current COVID-19 pandemic situation. This study aims to look at various strategies in overcoming obstacles to learning statistics during a pandemic. The writing of this article uses a literature study. There were 6 national journals indexed by Google Scholar. The analysis is done by looking at the differences and similarities of each article. The results showed that the application of learning strategies through learning video media, E-lumak, namely e-learning developed by the University of Muhamadyah Kendari, Whatsapp Group, Zoom Cloud Meeting application, virtual learning, and online learning based on Moodle were able to improve student learning outcomes. ABSTRAKMata kuliah statistika memiliki keunikan tersendiri dimata mahasiswa. Disatu sisi mata kuliah ini sangat penting dalam menunjang kegiatan penelitian di sisi lain masih dianggap sebagai mata kuliah yang sulit dipelajari. Kendala dalam mempelajari statistika semakin bertambah dengan adanya situasi pandemi covid-19 saat ini. Adapun tujuan penelitian ini adalah untuk melihat berbagai strategi dalam mengatasi kendala belajar statistika di masa pandemi. Penulisan artikel ini menggunakan studi literature. Diperoleh 6 jurnal nasional yang terindeks google scholar. Analisa dilakukan dengan melihat perbedaan dan persamaan dari masing-masing artikel. Hasil penelitian menunjukkan penerapan strategi pembelajaran melalui media video pembelajaran, E-lumak yaitu elarning yang dikembangkan oleh Universitas Muhamadyah Kendari, Whatsapp Group, aplikasi Zoom Cloud Meeting, pembelajaran virtual dan pembelajaran daring berbasis Moodle mampu meningkatkan hasil belajar mahasiswa.